Elastic Modulus Adjustment Method of Double-Stator HTS Field Modulated Machine Based on Entire Machine Modal Analysis - Yubin Wang; Chuntong Song; Zhiheng Zhang; Wei Hua (IEEE Access, 2024)
The double stator high-temperature superconducting field modulated (DS-HTS-FM) machine with a dual-stator configuration and high-temperature superconducting materials includes numerous cryogenic components that establish the required operating temperature for superconducting magnets. This abundance of cryogenic elements introduces complexity to the process of conducting a modal analysis of the entire machine. However, the conventional trial-and-error approach employed to achieve precise modal analysis results for the entire-machine suffers from the drawback of lacking a clear direction for adjustment elastic modulus which has a great influence on the modal analysis results. Therefore, it is difficult to obtain accurate modal analysis results of the entire-machine. In response to this challenge, this study focuses on a 10 kW DS-HTS-FM machine as its subject and presents an elastic modulus adjustment method based on the entire-machine modal analysis, aiming to obtain accurate finite element (FE) modal analysis results of the entire-machine. Initially, the FE method is used to find the components that have a great influence on the outer stator modals while the components that have less influence on the outer stator modal are equivalent to the front and rear end cover in the form of additional mass, thus establishing an entire-machine equivalent model for elastic modulus adjustment. Subsequently, an examination is conducted to ascertain the relative impact proportions of the elastic modulus associated with the outer stator, casing, end cover, and armature windings on the natural frequencies of the outer stator, which can lead to a precise determination of the optimal direction for adjusting the elastic modulus parameters. Lastly, based on the entire-machine modal experiment, the elastic modulus of the equivalent model is modified in a definite direction. Consequently, the elastic modulus values for various components of the DS-HTS-FM machine can be accurately identified. Experimental outcomes affirm the efficacy of this approach in attaining precise FE modal results for the DS-HTS-FM machine and reducing the computational time required for FE analysis.